Pemberdayaan Masyarakat melalui Pengajian Rutin untuk Penguatan Kesehatan Mental Berbasis Spiritual di Dusun Lobang, Kab. Batang - Ahmad Minan Zuhri; Zuhrotul Laili (Jurnal Medika: Medika, 2026)
Mental health in rural communities is not always clinically evident, but often manifests as anxiety, irritability, a lack of inner peace, and limited social space for sharing problems. This community service activity aims to strengthen spiritually-based mental health through religious guidance during regular religious studies in Lobang Hamlet, Sangubanyu Village, Bawang District, Batang Regency. The implementation method uses an Asset-Based Community Development (ABCD) approach, which includes strengths tracking, asset mapping, asset correlation, activity implementation, and evaluation and improvement. The main assets developed are regular religious studies, congregations, religious leaders, community leaders, mosques, prayer rooms, and community religious traditions. Activities are carried out through lectures, dialogues, questions and answers, reflections on experiences, and religious advice on the themes of patience, gratitude, trust in God, emotional control, peace of mind, and social support. The results of the activity indicate that regular religious studies function as a space for non-formal religious education, strengthening religious awareness, and providing psycho-spiritual support for the community. The congregation experiences benefits in the form of increased religious understanding, a calmer heart, the ability to control emotions, an attitude of patience and trust in God, and increased togetherness among residents. This activity demonstrates that regular religious study groups can be developed as a model for community-based spiritual empowerment to support the mental health of rural communities.